PENGARUH TOTAL QUALITY MANAGEMENT (TQM), GAYA KEPEMIMPINAN, KEDISIPLINAN KERJA DAN FUNGSI MENTORING TERHADAP KINERJA KARYAWAN PT. KEMAKMURAN BERKAH TIMBER SAMARINDA - Tipung, Dionesia Deska (EKONOMIA, 2018)
To be able improved Performance Employees in a company or organization, hence required by factors able to improve Performance itself. As for the factors is Totalizeing Quality Management, Style Leadership, Job Discipline and Function of Mentoring.This Formula research internal issue is" What is there Total influence of Quality Management, Style Leadership, Job Discipline and Function of Mentoring to Performance Employees. This Research aim to know Total influence of Quality Management, Style Leadership, Job Discipline and Function of Mentoring to Performance Employees. Method Research by using quesioner with scale of likert. Research population is entired all employees of PT. Kemakmuran Berkah Timber and of sampel research counted 45 employees people with technique intake of sampel that is totalizeing sampling.Analyzer the used multiple regression which where beforehand have  to test and validity of reliabilitas and also test classic assumption.Pursuant to result of solution and research hence Totalizeing Quality Management and Job Discipline have an effect on positive and significant to Performance Employees, so that Ho refused and Style Leadership not have an effect on positive and not significant, so that Ho accepted. While Function of Mentoring have an effect on positive but not significant to Performance Employees, so that Ho accepted. From result of this research expected can be used as by input to management side upon which consideration in order to make-up of employees performance.